Analisis Metode Aliran Permukaan Langsung (Direct Runoff) Sungai Way Besai Menggunakan Software HEC-HMS - Yana, Juwita Novi; Kusumastuti, Dyah Indriana; Winarno, Dwi Joko (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
The river is a gathering place for water in the surrounding environment which flows towards a lower place. Way Besai river is located in Sumberjaya sub-district, West Lampung district which has an area of 410.72 km2. Direct runoff needs to be carried out on the Way Besai river to determine the flood hydrograph that occurs in the Way Besai river. The HEC-HMS model is a numerical hydrological model developed by the Hydrologic Engineering Center (HEC) of the US Army Corps Of Engineers.The methods used in direct flow runoff in the HEC-HMS software are the SCS UH method, the Clark's UH method and the Snyder's UH method. The purpose of this research was to analyze the Way Besai river flood hydrograph by calculating direct runoff using these three methods. The results of this study indicate that the SCS UH method is the most suitable compared to Clark's UH method and Snyder's UH method because it produces the smallest deviation value. Keywords : Way Besai, direct runoff flow, HEC-HMS, SCS UH, Clark's UH, Snyder's UH